2009
DOI: 10.1002/bies.200800174
|View full text |Cite
|
Sign up to set email alerts
|

The DING family of proteins: ubiquitous in eukaryotes, but where are the genes?

Abstract: PstS and DING proteins are members of a superfamily of secreted, high-affinity phosphate-binding proteins. Whereas microbial PstS have a well-defined role in phosphate ABC transporters, the physiological function of DING proteins, named after their DINGGG N termini, still needs to be determined. PstS and DING proteins co-exist in some Pseudomonas strains, to which they confer a highly adhesive and virulent phenotype. More than 30 DING proteins have now been purified, mostly from eukaryotes. They are often asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 68 publications
(106 reference statements)
2
39
0
Order By: Relevance
“…Moreover, despite the biochemical properties allowed to correlate PARPSso to PARP enzymes, a first BLAST research of purified PARPSso towards classic PARPs was not fruitful: the structural analysis indicated that the sulfolobal enzyme had a different structure, resembling a new group of proteins, the DING proteins, Figure 2 [34][35][36].…”
Section: Parpsso Belongs To the Ding Protein Familymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, despite the biochemical properties allowed to correlate PARPSso to PARP enzymes, a first BLAST research of purified PARPSso towards classic PARPs was not fruitful: the structural analysis indicated that the sulfolobal enzyme had a different structure, resembling a new group of proteins, the DING proteins, Figure 2 [34][35][36].…”
Section: Parpsso Belongs To the Ding Protein Familymentioning
confidence: 99%
“…They belong to the superfamily of bacterial phosphate-binding proteins [35]. The phosphate-binding site is strongly conserved and comprises eight conserved or conservatively-substituted residues, responsible to hydrogen-bind the phosphate ion with high affinity [35].…”
Section: Parpsso Belongs To the Ding Protein Familymentioning
confidence: 99%
See 3 more Smart Citations